Flexible ternary carbon black/Bi2Te3 based alloy/polylactic acid thermoelectric composites fabricated by additive manufacturing - Yong Du; Jiageng Chen; Qiufeng Meng; Jiayue Xu; Biplab Paul; Per Eklund (Journal of Materiomics, 2020)
Flexible ternary carbon black/Bi2Te3 based alloy/polylactic acid (CB/BTBA/PLA) composites were fabricated by additive manufacturing and their thermoelectric properties were investigated from 300 K to 360 K. At 300 K, as the mass ratios of BTBAs in the composites increased from 38.5% to 71.4%, both the electrical conductivity and Seebeck coefficient of the composites increased from 5.8 S/cm to 13.3 S/cm, and from 60.2 μV/K to 119.9 μV/K, respectively, and the thermal conductivity slightly increased from 0.15 W m−1K−1 to 0.25 W m−1K−1, as a result, the ZT value of the composites increased from 0.004 to 0.023. As the temperature increased from 300 K to 360 K, the electrical conductivity of all the composites slightly decreased, while the thermal conductivity slowly increased, and a highest ZT value of 0.024 was achieved for the composites with 71.4% BTBAs at 320 K. Unlike traditional sterolithography, fused deposition modeling, selective laser melting, etc., this additive manufacturing process can directly print the solutions which contain inorganic fillers and polymer matrixes into almost any designed intricate geometries of thermoelectric composites, therefore this process has great potential to be used for fabrication of flexible polymer based thermoelectric composites and devices. Keywords: Flexible, Bi2Te3 based alloy, Additive manufacturing, Thermoelectric